Robust mask‐constrained linear array synthesis through an interval‐based particle SWARM optimisation. Issue 12 (1st September 2013) - Manica, Luca; Anselmi, Nicola; Rocca, Paolo; Massa, Andrea
Abstract : An innovative strategy for the robust design of linear antenna arrays is presented. Being the array elements characterised by tolerance errors, the synthesis is aimed at determining the intervals of values fitting the user‐defined mask constraints on the radiated power pattern. With reference to the upper and lower bounds of the power pattern analytically determined for given tolerances through interval analysis, the nominal excitations of the array elements are then optimised by means of a global stochastic optimiser suitably customised to deal with interval numbers. A set of numerical examples is reported to show the behaviour of the proposed method as well as to assess its potentials in dealing with the robust synthesis of pencil and shaped beams.